Impact of Maximizing Css/MIC Ratio on Efficacy of Continuous Infusion Meropenem Against Documented Gram-Negative Infections in Critically Ill Patients and Population Pharmacokinetic/Pharmacodynamic Analysis to Support Treatment Optimization - Cojutti, Pier Giorgio; Gatti, Milo; Rinaldi, Matteo; Tonetti, Tommaso; Laici, Cristiana; Mega, Chiara; Siniscalchi, Antonio; Giannella, Maddalena; Viale, Pierluigi; Pea, Federico (Frontiers in Pharmacology, 2021)
Introduction: optimal treatment of Gram-negative infections in critically ill patients is challenged by changing pathophysiological conditions, reduced antimicrobial susceptibility and limited therapeutic options. The aim of this study was to assess the impact of maximizing Css/MIC ratio on efficacy of continuous infusion (CI) meropenem in treating documented Gram-negative infections in critically ill patients and to perform a population pharmacokinetic/pharmacodynamic analysis to support treatment optimization. Materials and methods: Classification and regression tree (CART) analysis was used to identify whether a cutoff of steady-state meropenem concentration (Css)-to-minimum inhibitory concentration (MIC) (Css/MIC) ratio correlated with favorable clinical outcome. A non-parametric approach with Pmetrics was used for pharmacokinetic analysis and covariate evaluation. The probability of target attainment (PTA) of the identified Css/MIC ratio was calculated by means of Monte Carlo simulations. Cumulative fraction of response (CFRs) were calculated against common Enterobacterales, P. aeruginosa and A. baumannii as well. Results: a total of 74 patients with 183 meropenem Css were included. CART analysis identified a Css/MIC ratio ≥4.63 as cutoff value significantly associated with favorable clinical outcomes. Multivariate regression analysis confirmed the association [OR (95%CI): 20.440 (2.063-202.522); p<0.01]. Creatinine clearance (CLCR) was the only covariate associated with meropenem clearance. Monte Carlo simulations showed that, across different classes of renal function, dosages of meropenem ranging between 0.5 g and 2 g q6h over 6h (namely by CI) may grant PTAs of Css/MIC ratios ≥4.63 against susceptible pathogens with an MIC up to the EUCAST clinical breakpoint of 2 mg/L. The CFRs achievable with these dosages were very high (>90%) against Enterobacterales across all the classes of renal function and against P. aeruginosa among patients with CLCR <30 mL/min/1.73m2, and quite lower against A. baumannii. Discussion: our findings suggest that Css/MIC ratio ≥ 4.63 may be considered the pharmacodynamic target useful at maximizing the efficacy of CI meropenem in the treatment of Gram-negative infections in critically ill patients. Dosages ranging between 0.5 g q6h and 2 g q6h by CI may maximize the probability of favorable clinical outcome against meropenem-susceptible Gram-negative pathogens among critically ill patients having different degrees of renal function.